STUDENTS’ PERCEPTIONS OF INNOVATION IN SUSTAINABLE DEVELOPMENT TECHNOLOGIES AND THEIR ROLE TO OPTIMISE HIGHER EDUCATION’S QUALITY - Ben Brahim Neji, Hella; Besrour, Adel (BDC. Bollettino Del Centro Calza Bini, 2014)
Technological innovation and scientific research have always helped industry and other economic sectors to evolve, allowing them to reduce their production, operation and maintenance costs, and in return, the fields of engineering and innovation widened increasingly. The objective of this research is to evaluate the importance technological innovations in sustainable development (especially, green energy) on the quality of higher education improvement. The study is based on a survey conducted among a sample of students from the High School of Technology and Computer Sciences (ESTI – University of Carthage, Tunisia), pointing out the need to integrate teaching staff, researcher and students, in identifying and optimization technological solutions. Keywords: Technological innovation, contingent valuation method, energy saving